The future of Labour Law - Quiñones, Sergio (2017)
The premise of this paper is that the future of work will define the future of Labour Law, since work is indeed the main object of regulation of such legal discipline. From this perspective, we analyze the mega trends identified by the International Labour Organization that will continue to impact the world of work: globalization, the increase in the dependency rate, technological innovation and, above all, climate change. Likewise, the article addresses the main labor problems still facing Latin American countries, as well as the challenges that are presented in the near future to Peru in order to close the gap between the amount of employment generated in the country and the quality of said employment.